In-situ hydrodeoxygenation of furfural to furans over supported Ni catalysts in aqueous solution - Wang, Ze; Fu, Zhaolin; Lin, Weigang; Li, Songgeng; Song, Wenli (The Korean journal of chemical engineering, 2019)
In-situ hydrodeoxygenation of furfural as a representative component in bio-oil was investigated in aqueous solution over supported Ni catalysts, for preparing furans as an antiknock additive. The addition of methanol, ethanol, or isopropanol was found inhibitive to coke formation at 220 °C. When using methanol as the hydrogen donor and coke inhibitor, the support in mesoporous structure with moderate acidity was more favorable to the conversion of furfural and to the formation of furans. An increased loading amount of Ni facilitated the generation of deep hydrogenated products. The conversion of furfural could hardly be changed under different methanol to water ratios, while the product distribution varied remarkably. Under optimized conditions, the summary yield of furan and 2-methylfuran reached to above 85%. On the basis of optimized reaction conditions, the in-situ hydrodeoxygenation of an eight-component synthetic bio-oil was tested, and the results verified the adaptability of the method for conversion of bio-oil.